Investigation on Collision of Si^2+ with H from Intermediate to High Projectile Energies (Communications in Computational Physics, 2006)
Total and state-selective charge transfer, ionization and stripping cross sections due to the collision of Si2+ ion with atomic hydrogen are investigated using the classical-trajectory Monte-Carlo (CTMC) method in the collision energy from 1 keV/amu to 10 MeV/amu. Total electron capture rate coefficient is obtained in the temperature range from 105 Ko to 108 Ko. Comparison with the data available shows that our CTMC results are reliable. The behaviors for these cross sections varying with the projectile energy are analyzed. A classical physical picture is presented to explain the reason behind the behaviors.